Effect of probiotic on development of fingerling Kerai Lampam - Awang Khalid, Dayang Nurul Ainiah (2018)
Probiotic is a live microorganism, capable of improving health and growth if given to the right species of probiotic. This research was aimed to examine the effect of different probiotics on development of growth, survival and body composition of fingerling Kerai Lampam. The treatment used of this experiment is a completely randomized with three treatment which is two different species of probiotic and control that do not added probiotic. The fingerlings were immersed every seven days with two different species of bacteria, Bacillus pocheonensis and Lysinibacillus fusiformis with concentration of 106 CFUmL-1. The growth, survival and body composition parameters were measured prior and after one month of culture. According to the result, the growth and body composition showed no significance differences between the treatment (P> 0.05). However, it was relatively larger in the treatment treated with probiotic. Treated fish did not show any sign of infection during the experiment. In conclusion, both species of probiotic was not able to enhance the development of fingerlings Kerai Lampam.